Implementasi Metode Distribution Requirement Planning Pada Distributor Limbah Plastik Untuk Mengoptimalkan Biaya Distribusi - Bimanggala, Kelvin Loisura; Bamban Jakaria, Ribangun (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
The problem of plastic waste has become a serious global issue due to its negative impact on the environment. IKM K2 Recycle is a distributor of plastic waste, with an average sales volume of 50 tons per month and an average supply of raw materials of 80 tons per month. Companies often experience buildup in warehouses due to lack of effective control and planning. The purpose of this study is to optimize distribution costs and avoid buildup in warehouses with the Distribution Requirement Planning (DRP) method. Sales data carried out by forecasting is forwarded with distribution calculations by the DRP method. The calculation results with DRP were able to reduce distribution costs by Rp. 154,318,512 from the Company's previous calculation of Rp. 193,890,000. There is a decrease in distribution costs by a percentage of 20%. Thus, the company managed to optimize distribution costs and avoid the accumulation of goods in warehouses, which is a positive step to overcome the problem of plastic waste and negative environmental impacts.